(untitled) (Texas Journal of Medical Science, 2025)
This article examines the critical role of molecular dynamics (MD) simulations in investigating protein folding processes. Protein folding is a fundamental biological event through which a polypeptide chain attains its functional three-dimensional structure. Due to limitations of experimental techniques in capturing the rapid and complex folding events at atomic resolution, MD simulations provide a powerful computational approach to model the time-dependent conformational changes of proteins at the atomic level. The study explores various computational algorithms, force fields, and strategies used to analyze folding kinetics and energy landscapes. Additionally, the advantages and limitations of MD simulations, including high computational demands and timescale challenges, are discussed. The findings highlight the significance of MD as an effective tool for deepening the understanding of protein folding mechanisms and emphasize future directions for improving simulation accuracy and efficiency